Breastfeeding, nutrition and type 1 diabetes: a case-control study in Izmir, Turkey - Cicekli, Ipek; Durusoy, Raika (BMC, 2022)
Background The relationship between infant breastfeeding and type 1 diabetes mellitus (DM) is unclear but it has been suggested that there may be a link between many environmental factors, including dietary antigens affecting diabetes epidemiology. The main objective of this study is to investigate nutritional risk factors, especially breastfeeding early in life that may be associated with the development of type 1 DM and to determine the relationship these factors have with the disease. Methods This research is a case-control study and was carried out in Ege University Children's Hospital in Izmir, Turkey between 13 January 2020 and 5 March 2020. A total of 246 children aged between 4 and 14 years were included in the study. The case group consisted of patients diagnosed with type 1 DM followed-up by Ege University Children's Hospital's Endocrinology Unit and the control group included non-diabetic children attending the same hospital's General Pediatric Outpatient Clinic. A structured questionnaire was created by the researchers after reviewing the literature related to nutritional and other risk factors for type 1 DM. The questionnaire was administered by interviewing the parents and it was related to the child, mother and family of the child. In this study, breastfeeding duration was defined as the total duration of breastfeeding and exclusive breastfeeding meant that the child received only breast milk from the mother. Results The mean age at diagnosis was 6.30 +/- 4.03 years for cases and 7.48 +/- 2.56 years for controls. We found that each monthly increase in exclusive breastfeeding duration provided a 0.83-fold (95\% CI 0.72, 0.96) decrease in the risk of type 1 DM. Introduction of cereals in the diet at the sixth month or earlier was associated with a 2.58-fold (95\% CI 1.29, 5.16) increased risk. Conclusions Determining the contribution of exclusive breastfeeding to the disease is important in establishing preventive policies. A longer duration of exclusive breastfeeding may be an important role in preventing the disease. This free intervention that truly works will be cost-effective. Future studies are needed to clarify the role of both exclusive and non-exclusive breastfeeding on the development of type 1 DM.
Keywords: Diabetes mellitus; Risk factors; Breastfeeding; Infant; Diet; Child